NFC Based Toll Management System - Kelkar, Rohan; Bharambe, Abhishek; Prajapati, Akshaykumar; Kambli, Mansi (International Journal of Computer Sciences and Engineering, 2025)
The NFC based toll collection system can be used in places like toll-naka, police check-naka, license or vehicle paper checking, insurance and other vehicle related paper checking .It will be useful in reducing the time required for each vehicle at such places. This will help in reducing the jams and pollution caused by vehicles at places like highways. Architecture for collecting vehicles toll using Near Field Communication (NFC) is presented in this paper. This is a completely automated system where the driver just needs to swipe his card; no real money or other papers will be needed. A PC connected to the system will display the driver details. The booth-operators can also click on a button to collect the money from the driver. The money will be debited automatically from the card. After the tax is collected, the booth operators can then open or close the door. The performance of the system is evaluated in VB.NET.